2017
DOI: 10.3390/insects8010028
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Deformed Wing Virus in Deformed and Asymptomatic Honey Bees

Abstract: Deformed wing virus (DWV) in association with Varroa destructor is currently attributed to being responsible for colony collapse in the western honey bee (Apis mellifera). The appearance of deformed individuals within an infested colony has long been associated with colony losses. However, it is unknown why only a fraction of DWV positive bees develop deformed wings. This study concerns two small studies comparing deformed and non-deformed bees. In Brazil, asymptomatic bees (no wing deformity) that had been pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
37
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 43 publications
4
37
0
1
Order By: Relevance
“…Hence, this phylogenetic analysis did not help to easily answer the question whether DWV‐A or DWV‐B is more virulent but rather suggested considerable virulence differences within DWV‐A and ‐B. This result is consistent with a recent study that did also not find consistent differences between the entire DWV genomes from crippled or asymptomatic bees (Brettell et al ., ). However, the cited study might also have suffered from the fact that it cannot be excluded that the analyzed asymptomatic bees also included bees which only looked healthy but were actually suffering from a DWV‐B infection of the brain, hence, carried the virulent DWV‐B variant.…”
Section: Discussionmentioning
confidence: 97%
“…Hence, this phylogenetic analysis did not help to easily answer the question whether DWV‐A or DWV‐B is more virulent but rather suggested considerable virulence differences within DWV‐A and ‐B. This result is consistent with a recent study that did also not find consistent differences between the entire DWV genomes from crippled or asymptomatic bees (Brettell et al ., ). However, the cited study might also have suffered from the fact that it cannot be excluded that the analyzed asymptomatic bees also included bees which only looked healthy but were actually suffering from a DWV‐B infection of the brain, hence, carried the virulent DWV‐B variant.…”
Section: Discussionmentioning
confidence: 97%
“…Despite many decades of co-existence between honeybee, V. destructor and DWV, in millions of colonies and billions of honeybees world-wide, the pathology and virulence of DWV remain stubbornly linked to direct vectored transmission by V. destructor in developing pupae 14,[22][23][24][25]34 , with DWV pathology, virulence and titres all disappearing from honeybee colonies when varroa is removed 23,29 . This suggests that DWV genetic adaptation to transmission by V. destructor is either non-existent, and DWV virulence largely determined by the transmission route and viral titres 25 , or ephemeral; present only during varroa-mediated transmission with the DWV quasispecies rapidly returning to a default genetic shape and composition when varroa transmission is removed.…”
Section: Discussionmentioning
confidence: 99%
“…The principal varroa-transmitted virus is currently DWV 14 . There has long been a lively debate 19 as to whether the severe pathology caused by DWV is primarily due to genetic adaptation by the virus towards increased virulence [20][21][22] or due to excessive virus titres 17,[23][24][25] precipitated by this potent, novel transmission route [25][26][27][28] . Of course, these two alternatives are not mutually exclusive.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Damage to idiosoma can be crushed/broken, while leg damage can vary from the removal of the tip or apoteles to multiple legs leaving empty sockets. (Brettell et al, 2017) concluded that a high DWV load was the only consistent factor associated with wing damage. This latter study also found that using RT-PCR, deformed bees contained the highest viral loads, which is consistent with the findings here.…”
Section: Discussionmentioning
confidence: 99%